PENGARUH KUALITAS SOFTWARE DAN KUALITAS INFORMASI TERHADAP LAPORAN KEUANGAN PEMERINTAH KOTA BENGKULU - silva delvia; pakri Fahmi (Jurnal Ilmu Akuntansi, 2020)
The aim to be achieved in this study is to determine the effect of information quality and software quality on the financial reports of the Bengkulu City Government. The type of data used is data, namely data obtained from field studies and literature studies. Research respondents were financial management staff at Regional Apparatus Organizations (OPD) in Bengkulu City consisting of Budget User Proxy (KPA), Financial Administration Officials (PPK), Expenditure Treasurer and SIMDA Operators totaling 144 people in 36 OPDs. The analytical method used is multiple linear regression analysis. Based on the results of data analysis and discussion as described in the previous chapter, several conclusions can be drawn, namely: (1) Taken together, the variables of accounting software quality and information quality have a significant effect on the quality of information on OPD financial statements in Bengkulu City; (2) Partially accounting software quality variables have a significant effect on the quality of OPD financial report information in Bengkulu City; and (3) Partially the information quality variable has a significant effect on the quality of OPD financial report information in Bengkulu City.